Analisis Faktor Yang Mempengaruhi Keinginan Berwirausaha Pada Mahasiswa Perguruan Tinggi Isalm Swasta Di Kota Medan - Muhammad Arif; Willy Yusnandar (CERED Indonesia Institute, 2020)
This study aims to determine and analyze the effect of tolerance for risk, self-success and freedom in working partially on the desire to become entrepreneurs and to analyze the effect of tolerance for risk, self-success and freedom in working simultaneously on the desire to become entrepreneurial. This study uses an associative approach which is a study that aims to determine the relationship between several variables. This research was conducted on students at the Private Islamic College in Medan City. The population is all students at UMSU, UINSU and UISU. While the sample of this research is limited to students in semester 5 and 6. The sampling technique uses non-probability methods. Because of the large population, the sampling used a quota sampling technique of 100 students. Types of data collected to support the variables studied are primary data and secondary data. Data collection techniques used were interviews (Interview), a list of questions (Questionaire) and documentation study. The data analysis technique in this study used an associative approach and quantitative research with multiple linear regression statistical measures.Based on the results of research conducted, r table = 0.300. From the calculations in the study, it was obtained that B from tolerance to risk was 0.057, B Self-success was 0.015 and B freedom in work was 0.609. So it means that if the tolerance for risk is increased 100% (1 time) then the interest in entrepreneurship will increase by 5.7% and if self-success is increased 100% (1 time) then the interest in entrepreneurship will increase by 1.5% and if freedom in work is increased 100% (1 times) then the interest in entrepreneurship will increase by 60.9%